Current state of environmental awareness of transport service stakeholders and end-customers in the intermodal transport chain - Golnar, Marko; Beškovnik, Bojan (Transport, 2024)
Despite all the measures already taken and those still underway, pollution remains a major global problem, as the transport sector is the one where emissions are expected to increase in the coming years. Companies and policy makers are under increasing pressure to reduce the impact of their logistics activities in order to make transportation more environmentally friendly. One of the solutions to reduce emissions from intermodal transport is to choose the “right” mode of transport for each step in the transport chain. Such a measure increases the complexity of the transport chain and places an additional burden on transport companies in planning and organising transport for the entire transport chain. Additional difficulties arise from the fragmentation of information on emissions emitted for a single transport link and the lack of a unified approach to measuring and estimating transport chain emissions. As a result, this work finds that there is a lack of knowledge among users about the environmental impacts of transportation, despite the desire to contribute to greener transportation by paying more for a product or transportation service. The current research fills the gap in stakeholders’ understanding of the negative environmental impacts for individual transportation and for the entire transport chain. In addition, the study reveals a need for a systematically regulated and adapted way of informing users of intermodal transport chains due to the lack of transparency and comparison between different intermodal transport chains. To successfully address the challenges, the study proposes a 2-pillar approach. The 1st pillar approach focuses on designing a set of necessary measures (combination of top-down and bottom-up approach) for the transition to a low-carbon transport chain, while the 2nd pillar mainly focuses on mapping the level of green transport for easy comparison of similar products or services. The results of the research study show that the combination of numerical data with symbolic data is best suited to provide information on the level of green transport.